The effect of intellectual capital on job satisfaction of bank employees - Yuki Fitria, Muthia Roza Linda, (Opción, 2019)
This study carried out to determine and analyze the effects of human, structural and, customer capital on job satisfaction of bank employees in Padang. The primary data obtained from questionnaires and the data analysis technique was multiple linear regression analysis using by SPSS. The results showed that the ability of banks to educate employees through the use of human capital and a good relationship between the company and its partners through the application of customer capital had a significant influence on the job satisfaction, but the application of structural capital on banks did not have a significant effect on it.